2009
DOI: 10.1530/rep-08-0340
|View full text |Cite
|
Sign up to set email alerts
|

Pre-fertilization zona pellucida hardening by different cross-linkers affects IVF in pigs and cattle and improves embryo production in pigs

Abstract: Zona pellucida (ZP) hardening (resistance to proteolysis) has been classically identified as a post-fertilization event that contributes to the block to polyspermy. Di-(N-succinimidyl)-3,3 0 -dithiodipropionate (DSP), a permeable amine-reactive cross-linker, was recently shown to induce pre-fertilization ZP hardening and to improve porcine IVF productivity. The objectives of this study were to investigate i) how DSP affects pre-fertilization ZP hardening and IVF in cattle, ii) if a non-permeable amine-reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In vitro oocyte maturation and IVF were made as we have previously described (Canovas et al, 2009), with minor modifications. Groups of 30–40 mature bovine oocytes were transferred to wells containing IVF media and 25 µl of penicillamine–hypotaurine–epinephrine mix was added to each well ∼30 min before insemination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro oocyte maturation and IVF were made as we have previously described (Canovas et al, 2009), with minor modifications. Groups of 30–40 mature bovine oocytes were transferred to wells containing IVF media and 25 µl of penicillamine–hypotaurine–epinephrine mix was added to each well ∼30 min before insemination.…”
Section: Methodsmentioning
confidence: 99%
“…For the IVF experiment, the semen samples were processed by a Percoll gradient and incubated with or without exogenous DNA before being used in our standard IVF system (Canovas et al, 2009). In 3 replicates, 237 oocytes in the control group and 215 oocytes in the DNA group were inseminated.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, intramolecular disulphide bonds in ZP2 and intra‐ and intermolecular disulphide bonds in ZP4 are formed during fertilisation in the cow and pig (Iwamoto et al , 1999; Topfer‐Petersen et al , 2008), probably making the ZP much less porous or accessible to proteolytic enzymes. It also has been observed that treatment of oocytes with a crosslinking reagent [Di‐ (N‐succinimidyl)‐3,3′‐dithiodipropionate (DSP)] which forms bonds between the NH 2 groups of proteins increases ZP resistance to pronase digestion and to sperm penetration in the pig and cow (Coy et al , 2008 b ; Cánovas et al , 2009). For these reasons, the block to polyspermy and the hardening of the ZP have been associated with the formation of new bonds among proteins (Iwamoto et al , 1999; Topfer‐Petersen, Ekhlasi‐Hundrieser & Tsolova, 2008) and with changes in the secondary structure of the zona proteins (Nara et al , 2006) that take place at fertilisation and could modify the accessibility of the ZP receptors for spermatozoa and proteolytic enzymes.…”
Section: The Zona Block To Polyspermy In Mammalsmentioning
confidence: 99%
“…Following fertilization of the first sperm, the ZP is normally modified by cortical‐granule contents in a process called “hardening,” which prevents the binding and penetration of additional sperm (Vincent et al, ). In some species, artificial induction of ZP hardening can reduce the rate of polyspermy and improve embryonic development (Coy et al, ; Canovas et al, ). According to Edwards et al, (), heat stress during in vitro maturation induced the rate of dispersed cortical granules.…”
Section: Discussionmentioning
confidence: 99%